Caracterização e identificação de bactérias diazotróficas associativas oriundas de área de mineração de ferro - Pinto, Juliana Volpi Emrich (2017)
The soil is an environment severely affected by human activities such as agriculture, farming, urbanization and mining that causes its degradation. For instance, mining is responsible for the removal, exposure and contamination of the soil, reduction of vegetation, decrease or even extinction of biodiversity. Mining activity is essential for modern life, for the socioeconomic development of a country, so it needs to function in a sustainable manner. Diversity survey before the degradation processes generated by the mining industry is essential for later rehabilitation of these areas. Many methods are used for the rehabilitation of degraded areas, the main one being revegetation with native species or not, which can be potentiated when combined with inoculated microorganisms. Microorganisms responsible for biological processes of high relevance such as biological fixation of nitrogen mediated by diazotrophic bacteria, and the production of hormones, siderophores and increased resistance to pathogens also linked to these bacteria are very important for a positive response in the rehabilitation of these areas and the stability of the plant species inserted therein. The number of studies with associative diazotrophs in areas of iron mining is still deficient. The objective of this work was to isolate, characterize and identify associative diazotrophic bacteria from four areas in the Quadrilátero Ferrífero. The soil was collected in four different phytophysiognomies: Atlantic Forest, Cerrado, Canga and Capim. The isolates were obtained through soil solution and inoculated in semi solid medium NFb and FAM, repeated successive times in Pettri plates with the same solid media until obtaining pure colonies. We obtained 37 isolates with representatives in all areas except Atlantic Forest. Both media favored bacterial growth typical of diazotrophs, but not only associative, also legume lnodulating and endophytic bacteria. The phenotypic characterization was through cultural characterization in potato medium and identification through the partial sequencing of the 16S rDNA gene. There was a predominance of Burkholderia and Gluconacetobacter diazotrophicus, being the greatest diversity and density from the Capim phytophysionomy. The genera and species obtained in this work can be used in future studies with biotechnological and environmental interest.